1997
DOI: 10.1021/la970003y
|View full text |Cite
|
Sign up to set email alerts
|

Associating Polyelectrolytes with Perfluoroalkyl Side Chains:  Aggregation in Aqueous Solution, Association with Surfactants, and Comparison with Hydrogenated Analogues

Abstract: Derivatives of poly(sodium acrylate) bearing a few mole percent of perfluoroalkyl side chains were synthesized. Their solution properties were investigated by rheology and compared to those of their hydrogenated analogues. As the hydrogenated modified polymers, these new materials display an associating behavior. In semidilute solution the modified polymer exhibits viscosities of several orders of magnitude higher than the unmodified poly(sodium acrylate). However, this viscosifying effect is more pronounced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
2
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 35 publications
12
81
2
1
Order By: Relevance
“…Thus, the higher the comonomer content, the lower the C*, for example, the C* decreases to 2 wt.-% for the FA-200 copolymer with a comonomer content of about 1.6 mol-% for FA series and to 1 wt.-% for FMA-200 copolymers with similar mole percent of comonomer for FMA series. Similar trends were found by Iliopoulos et al [22] for both the hydrocarbon and fluorocarbon modified poly(sodium acrylate). As mentioned above, they used the polymer reaction to synthesize the modified PAA using PAA (MW L 10 5 ) reacts with alkyl R H or R F amine and confirmed that the molecular weight of modified PAA was not degraded after the reaction by GPC and the alkyl R F group was C8F as similar length as we used in comonomers of FA or FMA (C8F was 1CH 2 C 7 F 15 and ours is 1C 8 F 17 ).…”
Section: Semi-dilute Solution Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the higher the comonomer content, the lower the C*, for example, the C* decreases to 2 wt.-% for the FA-200 copolymer with a comonomer content of about 1.6 mol-% for FA series and to 1 wt.-% for FMA-200 copolymers with similar mole percent of comonomer for FMA series. Similar trends were found by Iliopoulos et al [22] for both the hydrocarbon and fluorocarbon modified poly(sodium acrylate). As mentioned above, they used the polymer reaction to synthesize the modified PAA using PAA (MW L 10 5 ) reacts with alkyl R H or R F amine and confirmed that the molecular weight of modified PAA was not degraded after the reaction by GPC and the alkyl R F group was C8F as similar length as we used in comonomers of FA or FMA (C8F was 1CH 2 C 7 F 15 and ours is 1C 8 F 17 ).…”
Section: Semi-dilute Solution Propertiessupporting
confidence: 88%
“…They also reported that fluorocarbon modified poly(sodium acrylate) shows an even more pronounced hydrophobic association. [22] However, these polymers were synthesized by post-polymerization of poly(acrylic acid) (M -n = 150 000) with long chain R H or R F alkylamines, and a random distribution of alkyl groups was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…85,86 Polyelectrolytes partially modified by hydrophobic groups have also been intensely studied. [87][88][89][90][91] Associative groups form aggregates, or micelles, through hydrogen bonds, ionic attraction, hydrophobic interaction, etc. Polymers with associative interactions exhibit a variety of condensed phases, typical examples of which are microscopically ordered phases, gels, and liquid crystals.…”
Section: Thermoreversible Gelation With Multiple Junctionsmentioning
confidence: 99%
“…Polímeros hidrofobicamente modificados e que são solúveis em água têm encontrado um grande número de aplicações práticas nos últimos 20 anos [1] . Devido à alta capacidade que possuem de aumentar a viscosidade do meio aquoso, eles podem ser utilizados nas mais diversas áreas, como, por exemplo, em tintas, cosméticos e processos de recuperação melhorada de petróleo.…”
Section: Introductionunclassified